Assessing Academic Writing Instruction: A Case Report Involving Radiologic Science Graduate Students. - Clark, Kevin R.; Watts, Lynette K. (Radiologic Science & Education, 2018)
Academic writing is an integral part of many graduate and doctoral programs. As future scholars in their fields of expertise, graduate and doctoral students must effectively disseminate findings to diverse audiences in a variety of venues. This case report presents a project assessing academic writing instruction in a radiologic science graduate program. Specifically, the writing instruction included completion of a synthesis matrix activity, participation in a jigsaw puzzle citation competition, and identification of common writing errors in sample papers. By acquiring suggestions about how to improve instruction from the graduate student participants, this case report details how changes to the writing instructional strategies assisted students in developing and strengthening their writing skills while promoting scholarly productivity.